The View from everywhere: temporal self-experience and the Good Life - Schechtman, Marya (Ethical theory and moral practice, 2024)
It is a common thought that our experience of self in time plays a crucial role in living a good human life. This idea is seen both in views that say we must think of our lives as temporally extended wholes to live well and those that say living well requires living in the moment. These opposing views share the assumption that a person’s interests must be identified with either a temporally extended or temporally local perspective. David Velleman has argued that both perspectives are necessary parts of human experience, and each has its own independent interests. I agree with Velleman that our experience is inherently multi-perspectival but argue that there are more than two relevant perspectives and reject the claim that these perspectives have independent interests. Expanding his metaphor of narrative, I describe the way in which these perspectives continuously influence and affect one another, and suggest that living well can be understood in terms of skillful management of the perspectives that make up this complex form of temporal self-experience.